Thermal energy storage : systems and applications - Dinçer, Ibrahim, 1964-; Rosen, Marc (Marc A.), ....- (Chichester : Wiley, 2002)
General Introductory Aspects for Thermal Engineering Energy Storage Systems Thermal Energy Storage (TES) Methods Thermal Energy Storage and Environmental Impact Thermal Energy Storage and Energy Savings Heat Transfer and Stratification in Sensible Heat Storage Systems Modeling of Latent Heat Storage Systems Heat Transfer with Phase Change in Simple and Complex Geometries Thermodynamic Optimization of Thermal Energy Storage Systems Energy and Exergy Analyses of Thermal Energy Storage Systems Thermal Energy Storage Case Studies A. Conversion Factors B. Thermophysical Properties C. Glossary Subject Index
Keywords: Heat storage; Warmteopslag